The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m512616200
|View full text |Cite
|
Sign up to set email alerts
|

Additional Sex Comb-like 1 (ASXL1), in Cooperation with SRC-1, Acts as a Ligand-dependent Coactivator for Retinoic Acid Receptor

Abstract: Additional sex comb-like 1 (ASXL1, 170 kDa), a mammalian homolog of Drosophila ASX, was identified as a protein that interacts with retinoic acid receptor (RAR) in the presence of retinoic acid (RA). Systematic binding assays showed that the C-terminal nuclear receptor box (LVMQLL) of ASXL1 and the activation function-2 activation domain (AF-2 AD) core of the RAR are critical for ligand-dependent interaction. The interaction was confirmed using in vitro glutathione S-transferase pulldown and in vivo immunoprec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
120
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 49 publications
(46 reference statements)
2
120
0
2
Order By: Relevance
“…BAP1 was also shown to deubiquitinate and stabilize some of its interacting partners, including HCF-1 and OGT indicating the functional importance of its catalytic activity (19,22,23). ASXL1/2 contain two uncharacterized N-terminal domains, ASXN and ASXM, and a C-terminal plant homeodomain finger (36,41). Interestingly, the DUB activity of a BAP1 family member, UCH37, is stimulated by RPN13 (ADRM1) 19S proteasome subunit (42)(43)(44), and phylogenetic studies suggest that RPN13 and ASXL1/2 share a conserved domain termed the DEUBiquitinase ADaptor (DEUBAD) domain corresponding to ASXM (45).…”
mentioning
confidence: 99%
“…BAP1 was also shown to deubiquitinate and stabilize some of its interacting partners, including HCF-1 and OGT indicating the functional importance of its catalytic activity (19,22,23). ASXL1/2 contain two uncharacterized N-terminal domains, ASXN and ASXM, and a C-terminal plant homeodomain finger (36,41). Interestingly, the DUB activity of a BAP1 family member, UCH37, is stimulated by RPN13 (ADRM1) 19S proteasome subunit (42)(43)(44), and phylogenetic studies suggest that RPN13 and ASXL1/2 share a conserved domain termed the DEUBiquitinase ADaptor (DEUBAD) domain corresponding to ASXM (45).…”
mentioning
confidence: 99%
“…For example, ASXL1 can interact with retinoic acid receptor in the presence of retinoic acid and enhance the transcription of some genes while repressing that of others, depending on the cell context. 15 The fine details of the mechanism of action of ASXL1 are not well defined yet, but the protein is involved in distinct multiprotein complexes that bind to and modify chromatin at target gene regions. Scheuermann et al demonstrated that ASXL1 exists in a complex, named polycomb repressive deubiquitinase, with BAP1, a ubiquitin carboxy-terminal hydrolase that removes monoubiquitin from histone 2A in nucleosomes.…”
mentioning
confidence: 99%
“…The primers used were (forward) 5 0 -GGGAGATTGGTTCAATGTCC-3 0 and (reverse) 5 0 -CCTGGAGCACCTAGACACCC-3 0 . For specificity, a primer set encompassing RAR response element in p21WAF1 promoter was used as described (Cho et al, 2006).…”
Section: Wb and Ip Analysismentioning
confidence: 99%
“…After 24 h, the cells were treated with 2.5 mg/ml cisplatin (Amersham Pharmacia Biotech). The effect of cisplatin on cell growth was monitored by MTT (Sigma) assay as described earlier (Cho et al, 2006). For apoptosis assay, H1299 cells were transiently transfected with p53, p73a, AMPKa2 alone and together for 2 days.…”
Section: Mtt and Apoptosis Assaymentioning
confidence: 99%